Psychological treatments for mental disorders in adults: A review of the evidence of leading international organizations - Moriana, Juan Antonio; Gálvez-Lara, Mario; Corpas, Jorge (Clinical psychology review, 2017)
Most mental health services throughout the world currently regard evidence-based psychological treatments as best practice for the treatment of mental disorders. The aim of this study was to analyze evidence-based treatments drawn from RCTs, reviews, meta-analyses, guides, and lists provided by the National Institute for Health and Care Excellence (NICE), Division 12 (Clinical Psychology) of the American Psychological Association (APA), Cochrane and the Australian Psychological Society (APS) in relation to mental disorders in adults. A total of 135 treatments were analyzed for 23 mental disorders and compared to determine the level of agreement among the organizations. The results indicate that, in most cases, there is little agreement among organizations and that there are several discrepancies within certain disorders. These results require reflection on the meaning attributed to evidence-based practice with regard to psychological treatments. The possible reasons for these differences are discussed. Based on these findings, proposals to unify the criteria that reconcile the realities of clinical practice with a scientific perspective were analyzed. •The evidence-based psychological treatments are the best practice for the treatment of mental disorders•There is lack of consensus in the evidence presented by different organizations•High degree of agreement was found for some disorders, while significant discrepancies were found for others•23 different treatments for depression have proven effective according to the organizations studied•Proposals to unify and improve the criteria that reconcile the clinical practice with a scientific view were analyzed